1930
DOI: 10.1002/hlca.19300130622
|View full text |Cite
|
Sign up to set email alerts
|

Röntgenographische Untersuchungen der basischen Chloride des Magnesiums. Zur Kenntnis der Magnesiumoxyd‐Zemente III

Abstract: Es wurden mehrere aus der Lösung isolierte basische Chloride verschiedener Zusammensetzung und Darstellungsart, sowie verschiedene Proben von erhärtetem Sorel‐Zement nach der Debye‐Scherrer‐Methode röntgenographisch untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1933
1933
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…However, the 3 phase is not the only phase formed during the formation of MOC cements. A series of articles by Feitknecht from 1926 to 1930 analyzed the formation of MOC phases with varying MgCl 2 concentrations and postulated that various phases (including 3–1–10 and 5–1–10) were forming, based on the first optical micrographs of needle-like crystals of MOC phases (as shown in Figure ) and X-ray diffraction patterns for these phases. In 1944, Feitknecht and Held again confirmed the existence of the 5 phase and revised the description of the crystalline water content within the composition to 5Mg­(OH) 2 ·MgCl 2 ·7H 2 O, which is now known as the 5 phase.…”
Section: Magnesium Oxychloride (Sorel) Cementsmentioning
confidence: 99%
“…However, the 3 phase is not the only phase formed during the formation of MOC cements. A series of articles by Feitknecht from 1926 to 1930 analyzed the formation of MOC phases with varying MgCl 2 concentrations and postulated that various phases (including 3–1–10 and 5–1–10) were forming, based on the first optical micrographs of needle-like crystals of MOC phases (as shown in Figure ) and X-ray diffraction patterns for these phases. In 1944, Feitknecht and Held again confirmed the existence of the 5 phase and revised the description of the crystalline water content within the composition to 5Mg­(OH) 2 ·MgCl 2 ·7H 2 O, which is now known as the 5 phase.…”
Section: Magnesium Oxychloride (Sorel) Cementsmentioning
confidence: 99%
“…Robinson and Waggaman 24 concluded that when MgO was in excess, 3MgOÁMgCl 2 Á10H 2 O was the stable hydration product formed in the MgO-HCl-H 2 O system at 25 C. Phase 3 was considered as the main binding phase, 25,26 and the composition of phase 3 was determined as 3Mg (OH) 2 ÁMgCl 2 Á8H 2 O. 27 Based on the optical micrographs of needle-like crystals of MOC phases and X-ray diffraction patterns, Feitknecht [28][29][30] analyzed the formation of MOC phases with varying MgCl 2 concentrations and postulated that various phases including 3-1-10 and 5-1-10 were formed. In 1944, the existence of the phase 5 was confirmed 31 and the composition of phase 5 was described as 5Mg(OH) 2 ÁMgCl 2 Á7H 2 O.…”
Section: Phase Composition In Mgo-mgcl -H O Systemmentioning
confidence: 99%
“…The main focus is on the system Mg(OH) 2 –MgCl 2 –H 2 O as it represents the scientific base for the production of magnesia cement (Sorel cement). Different basic magnesium chloride hydrates with the composition of x Mg(OH) 2 · y MgCl 2 · z H 2 O, where x – y – z = 3–1–8, 5–1–8, 9–1–4, 2–1–4, 2–1–2, and 3–1–0, were characterized, and their crystal structures were determined. …”
Section: Introductionmentioning
confidence: 99%